Fine Scale Influence of Weather on Northern Bobwhite Abundance, Breeding Success, and Harvest in South Texas - Robert M. Perez; James F. Gallagher; Michael C. Frisbie (National Quail Symposium Proceedings, 2017)
Weather plays a substantial role in annual changes in populations of northern bobwhite (Colinus virginianus) within and among ecological regions. Few studies have tested this relationship within the confines of specific sites. We examined the fine scale influence of annual (12-month), seasonal (6-month), and monthly Modified Palmer Drought Severity Indices (PMDI) and raw precipitation on abundance, breeding success, and harvest of northern bobwhites on 2 sites in south Texas. We used 18 years (1984–01) of roadside census, juvenile : adult ratios, and harvest records from the Chaparral Wildlife Management Area (CWMA) in La Salle County and 15 years (1984–99) of juvenile : adult ratios and harvest records from a private property in Brooks County (BCP) to examine relationships and trends with weather variables. Bobwhite abundance was correlated (r >= 0.50, P <= 0.035) with 12- and 6-month sums of precipitation and PMDI. Breeding success was correlated (r >= 0.53, P <= 0.023) with 12-month precipitation for both sites and was correlated (r = 0.53, P = 0.040) with 6-month precipitation for BCP only. Harvest variables for CWMA were correlated (r >= 0.54, P <= 0.022) with 12- and 6-month PMDI, while BCP harvest/ha was correlated (r = 0.54, P = 0.027) with the 12-month precipitation sum. Monthly correlates with precipitation increased from spring to summer until July when they became negatively related to rainfall on both sites. Monthly PMDI correlates became increasingly important from spring through summer including July. Our findings account for at least part of the annual variation in northern bobwhite abundance in south Texas and provide information useful in understanding of the influence of weather at fine spatial scales.
Keywords: abundance; breeding success; Colinus virginianus; harvest; Modified Palmer Drought Severity Index; northern bobwhite; precipitation; south Texas; weather